EXISTENCE OF SALAFIYYAH ISLAMIC BOARDING SCHOOL IN THE MIDDLE ERA OF INDUSTRIAL REVOLUTION 4.0 - Samudra Eka Cipta Heryana (Jurnal PPI Dunia, 2020)
This research is a study that examines how pesantren as an Islamic educational institution in Indonesia is able to survive amid the current modernization of pesantren education that changes the education system from traditional to modern. In this study there are several formulations of the problem, namely: 1) how was the initial development of Al-Barokah pesantren education, 2) how was the strategy of using the applied learning methods and models, 3) how was the final evaluation process at the Al-Barokah Islamic boarding school?. This research uses the content study method or literature study using several written studies and the use of qualitative methods in writing this article.